Circular Economy Analysis Service Quality with Price Intervening on Customer Loyalty of Coastal MSMEs in East Java - Dyah Eko Setyowati; Sri Kartika Sari Antariksa; Herman Herman; Susanto Susanto; Dian Ananta; Sutardi Sutardi (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The purpose of this study is to determine how to optimize the circular economy in the seafood processing industry in East Java. The circular economy is a complex concept, but it is essential to understand if we want to build a more sustainable future in coastal areas. How can applying appropriate technology to the processing of mussels as a processed seafood product become a circular economy campaign to increase ecopreneurship among MSMEs living around coastal areas and strengthen the competitiveness of MSME products in coastal areas? This research was conducted using a quantitative approach, with data collected through the distribution of questionnaires and interviews. This study uses Smart PLS as a testing tool and analyzes it both theoretically and practically to obtain the right solution. The research object is located in Sidoarjo, East Java. Primary and secondary data are the data sources used. The data collection method uses a Likert scale questionnaire. The variables studied: X1 implementation of a circular economy, X2 service quality, price as a mediator variable Z, and customer loyalty as a variable Y. The purpose of this study is to determine the effects of applying a circular economy on Service Quality and Customer Loyalty, with Price as an intervening factor. This study used a survey method, which gathers information by compiling a list of statements from respondents. In survey research, researchers examine the nature or causal relationships of variables without intervening. The results showed that implementing a circular economy in the processing of Kupang clams significantly affects customer loyalty, both directly and indirectly. Therefore, maritime seafood industry players should improve the circular economy in their production processes. Meanwhile, service quality and price also significantly influence customer loyalty.